PRE-HOSPITAL EMERGENCY CARE IN SWEDEN - Ulf BJÖRNSTIG (IATSS Research, 2004)
Traffic injuries cause a heavy burden on society in most motorized countries. Pre-hospital and hospital trauma care may have a potential to reduce these losses. By tradition the pre-hospital ambulance care has not until the last decades been integrated in the medical sector organization in Sweden. Nowadays it is regarded as the extended arm of trauma care. Improved qualification level to Registered Nurse (R.N.) and structured education and training has improved the competence of the pre-hospital personnel. However, few objective studies of the effect are available. The National Board of Health and Welfare publish national guidelines for pre-hospital care and disaster management and support economically training in mass casualty and disaster command and control. Systemized training of rescue and ambulance teams in co-operation at a crash site may reduce the extrication time of entrapped car/truck crash victims by 40–50 per cent. This is a valuable time gain especially in a cold climate, which may add hypothermia problems to the injuries. In Sweden (9 million inhabitants), a sparsely populated country with sometimes long transportation distances to the nearest trauma hospital, 800 ambulances, 7 ambulance helicopters and 3–5 fixed wing ambulance aircraft are the available transport resources. In case of a mass casualty or disaster situation, inside or outside the country, a governmental project (Swedish National Medevac) aims to convert a passenger aircraft from Scandinavian Airlines System (SAS) to a qualified medical resource for long distance transport, with capacity to nurse six intensive care patients and an additional 6–20 lieing or seated patients during transport.